Plato: The las days of Sócrates - Tredennick, Hugh (Londres, Inglaterra : Penguin Books, 1969)
The trial and condemnation of Socrates (469-399), on Charges of heresy and corrupting the minds of the young, forms one of the most tragic episodes in the history of Athens in decline.
CONTENTS Introduction Socrates in action: EUTHYPHRO Sócrates on Trial: THE APOLOGY Sócrates in Prison: CRITO The last conversation: PHAEDO Notes to Euthyphro Notes to The Apology Notes to Crito Notes to Phaedo Select Bibliography
Incluye Contenido
Incluye Bibliografía
Keywords: FILÓSOFOS; FILÓSOFOS ANTIGUOS